Reconstructing smoking history through dental cementum analysis - a preliminary investigation on modern and archaeological teeth. - Valentina Perrone; Anna M Davies-Barrett; Mario Migliario; Patrick Randolph-Quinney; Sarah A Inskip; Edward C Schwalbe (PLoS ONE)
Acellular extrinsic fibre cementum (AEFC) has been widely utilised in cementochronology to estimate age at death, seasonality, and for life-history reconstruction. Smoking has been commonplace in the UK since the 17th century and is known to compromise oral health and to modulate physiological processes. This study aimed to investigate whether AEFC analysis could identify smoking activity in both modern and archaeological populations. A modern sample (70 teeth from 46 donors) with known age, sex, and smoking status was compared with an archaeological sample (18 teeth from 18 individuals), dating from the 18th/19th centuries in Coventry, UK, whose biographical information was recorded from coffin plates where available. Smoking status for the archaeological individuals was inferred from pipe notches and dental staining. AEFC analysis that was blinded to smoking status measured increment count, overall width and the presence of irregularities within the cementum microstructure in both samples. Results demonstrated that the AEFC width was significantly lower (p = 0.008) in current smokers compared to ex-smokers. Additionally, individuals with a history of smoking were significantly more likely to display disrupted incremental patterns within their AEFC (p < 0.001). This research suggests an association between smoking and periodontal ligament health, which influences AEFC formation and shows that the AEFC provides a record of smoking-related oral health damage. This research expands the potential applications of cementochronology to forensic and archaeological investigations for life history reconstruction.